2011
DOI: 10.1002/pssa.201001214
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring properties of borohydrides for hydrogen storage: A review

Abstract: Hydrogen is recognized as a possible future energy carrier, which can be produced from renewable energy and water. A major challenge in a future ‘hydrogen economy’ is the development of safe, compact, robust, and efficient means of hydrogen storage, in particular for mobile applications. The present review focuses on light metal boron based hydrides, for which the general interest has expanded significantly during the past few years. Synthesis methods, physical, chemical and structural properties of novel boro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
253
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(258 citation statements)
references
References 204 publications
3
253
0
2
Order By: Relevance
“…The decomposition temperature of the bialkali metal borohydrides like LiK(BH 4 ) 2 is approximately the average of the decomposition temperature of the mono alkali borohydrides (Rude et al, 2011). Investigations of Li et al and Seballos et al (Seballos et al, 2009) confirmed that this correlation between desorption enthalpy / observed T d holds true for many double cation MM'(BH 4 ) n systems, see Fig.…”
Section: Borohydridesmentioning
confidence: 73%
See 2 more Smart Citations
“…The decomposition temperature of the bialkali metal borohydrides like LiK(BH 4 ) 2 is approximately the average of the decomposition temperature of the mono alkali borohydrides (Rude et al, 2011). Investigations of Li et al and Seballos et al (Seballos et al, 2009) confirmed that this correlation between desorption enthalpy / observed T d holds true for many double cation MM'(BH 4 ) n systems, see Fig.…”
Section: Borohydridesmentioning
confidence: 73%
“…However, no clear indicative experimental results for F --substitution in borohydrides are found yet. In contrast to the F the heavier and larger halides Cl, Br, I are found to readily substitute in some borohydrides for the BH 4 --ion and form solid solutions or stoichiometric compounds and are so far reported to stabilize the hydride phase leading to an increase of the desorption enthalpy |H| (Rude et al, 2011). Fig.…”
Section: Borohydridesmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, several attempts have been recently carried out in order to promote hydrogen desorption and absorption processes. Because electronic structure calculations indicate that a charge transfer from the metal cations M n þ to the [BH 4 ] anions is a key feature determining the thermodynamic stability of M(BH 4 ) n , cation and anion substitutions in LiBH 4 have been investigated [3][4][5][6][7]. Moreover, a destablization of LiBH 4 via reaction with a second hydride system has been suggested, in order to reduce the Gibbs Free Energy (GFE) difference between hydrogenated and de-hydrogenated species [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a destablization of LiBH 4 via reaction with a second hydride system has been suggested, in order to reduce the Gibbs Free Energy (GFE) difference between hydrogenated and de-hydrogenated species [2,8]. As an example, LiBH 4 -MgH 2 reactive hydride composite has been deeply studied [5,9]. Even if the mechanisms of dehydrogenation reactions have not been clarified yet, the addition of a small amount of a promoter (e.g.…”
Section: Introductionmentioning
confidence: 99%